2023
DOI: 10.1007/s11104-023-06000-y
|View full text |Cite
|
Sign up to set email alerts
|

Plant-soil feedback: the next generation

Abstract: Plants can strongly influence the performance of subsequent conspecific and heterospecific plants either positively or negatively by conditioning soil abiotic and/or biotic properties via plant litter and root activity. This process is commonly known as 'plant-soil feedback', which has been increasingly demonstrated to play a major role in plant community dynamics, ecosystem succession, and the maintenance of biodiversity (e.g.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Plant performances during the response phase are measured to predict how soil microbes influence plant coexistence (Crawford et al ., 2019, Yan et al ., 2022). However, despite a vast body of literature showing that soil microbes can exert strong controls over plant species coexistence, connecting the predictions from such two-phase studies to the observed dynamics of plant communities in nature remains challenging (Forero et al ., 2019, Beals et al ., 2020, Beckman et al ., 2022, Png et al ., 2023). A promising approach for addressing this challenge is to adopt the classic two-phase design to better reflect the natural conditions under which PSF arises in the field (Gundale & Kardol, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Plant performances during the response phase are measured to predict how soil microbes influence plant coexistence (Crawford et al ., 2019, Yan et al ., 2022). However, despite a vast body of literature showing that soil microbes can exert strong controls over plant species coexistence, connecting the predictions from such two-phase studies to the observed dynamics of plant communities in nature remains challenging (Forero et al ., 2019, Beals et al ., 2020, Beckman et al ., 2022, Png et al ., 2023). A promising approach for addressing this challenge is to adopt the classic two-phase design to better reflect the natural conditions under which PSF arises in the field (Gundale & Kardol, 2021).…”
Section: Introductionmentioning
confidence: 99%